How Accounting Artificial Intelligence Can Prevent Fraud ? (Status and Research Opportunities) - Aloysius Harry Mukti; Triana Yuniati (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
The implementation of information technology is crucial as a fraud prevention mechanism, the industrial revolution has triggered the optimization of information technology that increasingly resembles humans or what we call artificial intelligence. Human has limitations in the capacity of data storage and analysis of decision making. The purpose of this study was to provide a description of the results of research related to artificial intelligence and the role of artificial intelligence in preventing fraud. The research method of this research is qualitative by conducting a literature review based on the results of previous studies without any classification criteria for journal sources. The results showed that the majority of research in this study still used a qualitative approach and literature reviews, it was rare that research conducted in-depth analysis or detailed case studies related to the implementation of artificial intelligence. The results also show that the application of artificial intelligence has never classified whether the artificial intelligence that has been implemented is weak or sophisticated artificial intelligence.